Propostas para a transposição didática: o grande desafio da educação lingüística - Abrão, Laura Garcia (2009)
A big challenge to a teacher is changing scientific knowledge into didactic content. To achieve this goal, complex theories have to be changed, without losing their properties and characteristics, to be assimilated by students. In this manner, the didactic transposition can be conceived as a body of acts that can change and become a wise knowledge to teaching knowledge , which brings in the core of the issue the conception that teaching can be built by the articulation of the academic competency plus pedagogic competency. In this context, we are able to see that inappropriate development of teachers impedes them from thinking about the didactic transposition practice and transforming it from expert awareness into instruction in behavior of Portuguese language. Here, we consider carefully the didactic transposition for an efficient teaching of Portuguese language. So we think about appropriate text theories of teaching Portuguese language and, assuming that universities don´t consider the didactic transposition, we have analyzed the Linguistics teaching courses of a public and private university searching for didactic transposition to apply in Portuguese lessons. We propose activities which go in the way of Linguistics education. It is possible to conclude that the supposition considered is true because the Linguistics courses that have been analyzed neither considered the didactic transposition nor the Linguistics education. So, we are able to conclude that didactic sequences are rich tools for teaching Portuguese language and, if used properly, it is possible to develop a work based on didactic transposition